CONCEPTUAL AND THEORETICAL PORTRAITS OF THE INCUBATION ACTIVITIES OF VETERINARY INCUBATION FOUNDATION (VIF) @ TANUVAS - C. Soundararajan; R. Vadivel (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Incubation centers are providing office spaces, access to advanced laboratory setups, farm facilities, clinical spaces, and comprehensive mentorship encompassing technical, legal, and financial guidance to the incubatees. The activities of VIF @ TANUVAS regarding areas of interest of 62 incubatees, products and productization, grants, ideas, and awareness programs were analysed for the period from 2019 to 2023. Among the area of interest of the incubatees, most of the incubatees (85 %) are working in the domain of Veterinary while 15% of the incubatees are working in the area of life sciences. Among the Veterinary related ideas, the majority of incubatees are interested in doing research in the development of diagnostic kits 26.41%, followed by Feed and Feed supplements (24.52%) whereas life sciences-related ideas are majorly chosen for drug discovery. Out of 62 ideas, 23 products were developed with a percentage of 37.1. Out of these 13 incubatees, 5 received grants (38.46%) from the Government of India (Central funds), while the remaining 8 (61.54%) received funding from the Government of Tamil Nadu (State funds). The highest number (52.81%) of ideas obtained during the year 2023 followed by 27.3% during 2021, 10.45% during 2020, and 9.41% during 2022 with more ideas from Madras Veterinary College, Chennai. This study concludes that The outcome of the product is directly proportionate to their ideas.